Sex differences in mortality risk and U-shaped relationship with klotho levels: A long-term cohort study - Junwen Wang; Lin Bai; Yuyang Ye; Xuefeng Chen; Xinru Hu; Yong Peng (Experimental Gerontology)
Backgrounds: It remains unclear whether there are sex differences in the correlation between klotho and mortality risk. The purpose of our study is to investigate the relationship between klotho levels and all-cause mortality, specifically examining potential sex disparities. Methods: The study utilized data from the National Health and Nutrition Examination Survey. The study employed the Cox proportional hazards model and Kaplan-Meier survival curves to conduct multivariate analyses investigating the associations between klotho and mortality. The impact of klotho level on mortality was assessed by a restricted cubic spline curve. Results: Our study included 13,748 participants. The hazard ratios (HR) for all-cause mortality were found to be higher in males compared to females. The risk of all-cause mortality decreased until the klotho level reached 959 pg/mL in all-cause mortality, then increased thereafter in females (P value for nonlinearity = 0.01, P overall = 0.02); no curved relationship was observed in males. Conclusion: Klotho levels and mortality follow a U-shaped curve, with sex differences in the relationship. Males with higher klotho levels have a higher risk of all-cause death than females.